Towards an Interdisciplinary Teaching Proposal for the Basic Core Curriculum in Bachelor’s Degrees in Economics - Di Russo, Leila (Ediciones UNL. Secretaría de Extensión de la UNL, 2020)
This work reviews some outcomes from the research process carried out for the thesis “Teaching sequences for the coordination of disciplines in the basic core curriculum of FCE-UNL”, written within the framework of the Master’s in University Teaching from FHUC-UNL. Some contrastive works and some other works based on the search for empirical evidence were taken from the thesis mentioned and they allowed researchers to analyse the current state of training of those students who finished the Basic Core Curriculum stage in FCE.Many times, current university education practices tend to “downplay” the importance of viewing knowledge as a whole. Teachers were asked to participate in surveys to gather information about their view. These were semi-structured, carried out in person and directly, and consisted in a questionnaire which triggered a deeper inquiry.Constant interaction with students from the Basic Core Curriculum years showed the need for a systemic approach in order to understand not only the issues related to the training of professionals for their future performance but also -and mainly- in order to prepare them to face the world and life in general with a consistent set of beliefs reinforced during theircomprehensive training in the Argentinian Public University.